Detection of epidermal growth factor-urogastrone and its receptor during fetal mouse development - Nexø, Ebba (1980)
Using both a radioimmunoassay and a radioreceptor assay, we have estimated the content of mouse epidermal growth factor-urogastrone (EGF-URO) in fetal mice at 11½ to 17½ days of gestation. Concurrently, the amount of specific EGF-URO receptor binding was determined in crude membrane fractions from the embryos. EGF-URO receptor binding is readily detected in membranes from the youngest embryos (day 11½) and rises steadily up to parturition (18 days); the rise is more marked in embryo membranes derived from a potential target tissue, such as the maxilla and secondary palate. In the embryonic extracts, EGF-URO proved to be labile, requiring the presence of soybean trypsin inhibitor and sodium azide to stabilize the recovery of added EGF-URO in test samples. Even with added stabilizing agents, immunoreactive EGF-URO was barely detectable before day 14½ (less than 20 fmol per embryo), whereas a substantial increase was observed from day 15½ to 17½ (from 70 to 200 fmol per embryo). In contrast, the radioreceptor assay detected appreciable amounts of an EGF-URO-like substance at 11½ days (50 fmol per embryo); the values estimated by radioreceptor assay (about 10-fold higher than by radioimmunoassay) also increase markedly between days 15½ and 17½ (on average from 500 to 3000 fmol per embryo). We conclude that during fetal mouse development there is an increase both in the receptors for EGF-URO and in a substance (presumably a fetal growth factor) that can occupy the receptor. The differences between the radioreceptor and radioimmunoassay estimates for the EGF-URO content suggest that the fetal form of mouse EGF-URO differs from the adult molecule.